PERAN PROMOSI DAN E-WALLET MEMODERASI PENGARUH KUALITAS WEBSITE PADA NILAI HEDONIK DAN PEMBELIAN IMPULSIF MARKETPLACE - Oktora Panasea, I Gede Nandya; Rsi Respati, Ni Nyoman; Mastama, Komang Riska Febyanti; Paramita, Ni Luh Dila Diah; Ningsih, Nova Widya; Putra, Agus Erik Wistika (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.05.TAHUN.2022DO - 10.24843/EEB.2022.v11.i05.p11, 2022)
The online buying and selling system causes a transition from the initial payment being made in cash, now turning into a non-cash payment using an e-wallet. One way to increase the number of e-wallet users is to carry out sales promotions. Sales promotion stimulants create a hedonic value that leads to impulsive shopping behavior in consumers. Therefore, the purpose of this study was to determine the effect of website quality moderated by sales promotion and use of e-wallet on hedonic value and online impulse buying from marketplace users. This study examines four variables, namely website quality, sales promotion, use of e-wallet, hedonic value and online impulse buying. This study took samples using a purposive sampling method with the target respondents being people who shopped at the marketplace more than 2 times. As for the number of respondents who were determined as many as 320 respondents.